A method for assessing recovery of fine motor function of the hand in a rhesus monkey model of cortical injury: an adaptation of the Fugl–Meyer Scale and Eshkol–Wachman Movement Notation. (2nd January 2019) - Pessina, Monica A.; Bowley, Bethany G. E.; Rosene, Douglas L.; Moore, Tara L.
Abstract: Motor dysfunction of the upper extremity can result from stroke, cortical injury and neurological diseases and causes significant disruption of activities of daily living. While some spontaneous recovery in terms of compensatory movements does occur after injury to cortical motor areas, full recovery is rare. The distinction between complete recovery and compensatory recovery is important as the development of compensatory movements in the upper extremity may not translate into full functional use in human patients. However, current animal models of stroke do not distinguish full recovery from compensatory recovery. We have developed a Non-Human Primate Grasp Assessment Scale (GRAS) to quantify the precise recovery of composite movement, individual digit action, and finger-thumb pinch in our rhesus monkey model of cortical injury. To date, we have applied this GRAS scale to assess the recovery of fine motor function of the hand in young control and cell-therapy treated monkeys with cortical injury confined to the hand representation in the dominant primary motor cortex. We have demonstrated that with this scale we can detect and quantify significant impairments in fine motor function of the hand, the development of compensatory function during recovery and finally a return to full fine motor function of the hand in monkeys treated with a cell therapy.